Locating the Traveller: Genni Gunn and Nostalgia on the Move - Terzian, Sylvia; Austen, Veronica (Italian Canadiana, 2021)
This paper analyzes the concept of nostos through a reading of Italian-Canadian writer Genni Gunn’s autobiographical travelogue Tracks: Journeys in Time and Place (2013) to show how its narratives of movement contest meanings of home and homecoming. Gunn initiates new ways of thinking about return by taking the migrant traveler as its central figure and envisioning home as a “practice of displacement” (Evelein 21) wherein “home” is not achievable through physical return, but through memory. Specifically, Gunn subverts traditional notions of home by reimagining Italy through her travels to foreign places, which ultimately serve as sites of return to her homeland via cartographies of memory. In Gunn’s exploration of nostalgia, her narrative presents her identity as an Italian-Canadian immigrant as no longer defined by national borders, but rather as a condition of movement. Gunn uses the framework of travel to link acts of homemaking and homefinding so that the meaning of nostos emerges as a kind of dwelling-in-displacement.